CONTRIBUTION TO THE PHYSICAL AND MECHANICAL CHARACTERIZATION OF TILES IN MICRO-CONCRETE MADE LOCALLY WITH THE GUM ARABIC. - BOZABE, R. Karba; TOUKOUROU, CHAKIROU A.; HOUNKONNOU, MAHOUTON NORBERT (My University, 2013)
The main objective of the present study is the validation of the use of a binder vegetable (gum Arabic) as matrix in the elaboration of the building materials of the semi-structural or structural components in the field of the cover of the works. It makes the synthesis of a set of results obtained on this binder and the structural elements made with this binder. Scientific and technical reference information of practical use will be put in the measure of the tile makers and the inhabitants of the dry and hot zones of the Sahel and Sahara for the production of quality tiles. We want to help these inhabitants to cover easily and at a lower cost their works. The interest of this study lives in the possibility of realizing through various experimental methods or digital simulation of the appropriate and relatively simple physical and mechanical tries on the semi-structural components (tiles) to know their behavior.
Keywords: binder vegetable; cover of the works; gum Arabic; matrix; quality tiles and semi-structural components.